A novel, multiplexed targeted mass spectrometry assay for quantification of complement factor H (CFH) variants and CFH‐related proteins 1–5 in human plasma. Issue 6 (March 2017) - Zhang, Pingbo; Zhu, Min; Geng‐Spyropoulos, Minghui; Shardell, Michelle; Gonzalez‐Freire, Marta; Gudnason, Vilmundur; Eiriksdottir, Gudny; Schaumberg, Debra; Van Eyk, Jennifer E.; Ferrucci, Luigi; Semba, Richard D.
Abstract : Age‐related macular degeneration (AMD) is a leading cause of visual loss among older adults. Two variants in the complement factor H (CFH) gene, Y402H and I62V, are strongly associated with risk of AMD. CFH is encoded in regulator of complement activation gene cluster in chromosome 1q32, which includes complement factor related (CFHR) proteins, CFHR1 to CFHR5, with high amino acid sequence homology to CFH. Our goal was to build a SRM assay to measure plasma concentrations of CFH variants Y402, H402, I62, and V62, and CFHR1‐5. The final assay consisted of 24 peptides and 72 interference‐free SRM transition ion pairs. Most peptides showed good linearity over 0.3–200 fmol/μL concentration range. Plasma concentrations of CFH variants and CFHR1‐5 were measured using the SRM assay in 344 adults. Plasma CFH concentrations (mean, SE in μg/mL) by inferred genotype were: YY402, II62 (170.1, 31.4), YY402, VV62 (188.8, 38.5), HH402, VV62 (144.0, 37.0), HY402, VV62 (164.2, 42.3), YY402, IV62 (194.8, 36.8), HY402, IV62 (181.3, 44.7). Mean (SE) plasma concentrations of CFHR1‐5 were 1.63 (0.04), 3.64 (1.20), 0.020 (0.001), 2.42 (0.18), and 5.49 (1.55) μg/mL, respectively. This SRM assay should facilitate the study of the role of systemic complement and risk of AMD.